The corpse in the Middle Ages: embalming, cremating, and the cultural construction of the dead body - Schmitz-Esser, Romedio (Harvey Miller Publishers, 2020)
"To what extent are the dead truly dead? In medieval society, corpses were assigned special functions and meanings in several different ways. They were still present in the daily life of the family of the deceased, and could even play active roles in the life of the community. Taking the materiality of death as a point of departure, this book comprehensively examines the conservation, burial and destruction of the corpse in its specific historical context. An ambivalent treatment of the dead body emerges, one which necessarily confronts established modern perspectives on death. New scientific methods have enabled archaeologists to understand the remains of the dead as valuable source material. This book contextualizes the resulting insights for the first time in an interdisciplinary framework, considering their place in the broader picture drawn by the written sources of the period, ranging from canon law and hagiography to medieval literature and historiography"-- Provided by publisher.
Keywords: Mittelalter; Feuerbestattung; Einbalsamieren; Leiche; Geschichte 500-1500; Kultur; Bestattungsritus; Totenkult